2012
DOI: 10.4193/rhino11.267
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal malignant melanoma: an analysis of 115 cases assessing outcomes of surgery, postoperative radiotherapy and endoscopic resection

Abstract: Background: Melanomas account for 4% of sinonasal malignancies. We present the largest single institution series reported thus far and analyze the outcome with reference to lymph node involvement, radiotherapy and endoscopic resection. Methodology: Survival and recurrence data were analyzed on sinonasal melanoma cases collected from 1963-2010 to compare treatment strategies and to ascertain factors predicting outcome. Results: 115 cases (mean age 65.9) were treated at our institution during this period. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 34 publications
(78 reference statements)
1
17
0
Order By: Relevance
“…Moreover, the observed 5-year OS rate of 55% for all SNMM in the present study agrees with and exceeds the OS previously reported by our group (that included a part of the present study population) [9]. The 55% OS rate also compares favourably to other studies that generally have indicated 5-year OS rates of less than 40% for SNMM [7,[10][11][12][13][14]. As discussed in our earlier publication [9], the differences might reflect our frequent utilization of neoadjuvant hyper-fractionated RT with concomitant chemotherapy or adjuvant RT following surgery for stage IVA SNMM.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the observed 5-year OS rate of 55% for all SNMM in the present study agrees with and exceeds the OS previously reported by our group (that included a part of the present study population) [9]. The 55% OS rate also compares favourably to other studies that generally have indicated 5-year OS rates of less than 40% for SNMM [7,[10][11][12][13][14]. As discussed in our earlier publication [9], the differences might reflect our frequent utilization of neoadjuvant hyper-fractionated RT with concomitant chemotherapy or adjuvant RT following surgery for stage IVA SNMM.…”
Section: Discussionsupporting
confidence: 90%
“…Of 320 initial search results, 61 full‐text articles were assessed for eligibility, and 35 studies were ultimately included for systematic review and meta‐analysis 17‐52 . A total of 952 patients were included.…”
Section: Resultsmentioning
confidence: 99%
“…Tumors are often detected at a late stage resulting in poor patient prognosis, with 5-year overall survival (OS) below 25%. [1][2][3] The standard of care comprises surgical resection, with comparable outcomes between open and endoscopic approaches in well-selected patients. 4,5 The efficacy of adjuvant radiotherapy and the use of systemic therapy are controversial.…”
Section: Introductionmentioning
confidence: 99%